La deuxième vie du doux commerce. Métamorphoses et crise d’un lieu commun à l’aube de l’ère industrielle - Arnault Skornicki (Astérion)
This article deals with a blind spot in Hirschman’s analysis in The Passions an the Interests: according to him, the topos of the doux commerce would have been erased from the collective consciousness during the 19th century, due to the social consequences of the industrial revolution. However, in the debates that animate the industrialist thinkers under the French Restoration (1814-1830), the association between civil peace and economic development takes on new topical and argumentative forms with the conceptual shift from the “trading nation” to the “industrial society”. This shift is not indifferent: it has reconfigured the topography of the doux commerce. On the one hand, the theme of peaceful industry superimposed the workshop model (regarded as cooperative, productive and hierarchical) on that of commercial exchange (regarded as more egalitarian). On the other hand, it opened the prospect not only of a simple softening, but of a radical substitution of interest for passions and of a total elimination of conflict thanks to the peaceful exploitation of nature. However, the emergence of the social question sowed discord among industrialists: without rejecting the commonplace entirely, the Saint-Simonians separated from the liberals by detaching the theme of peaceful industry from the dogma of free competition.